Volume 1: Heat Transfer in Energy Systems; Thermophysical Properties; Theory and Fundamentals in Heat Transfer; Nanoscale Therm 2016
DOI: 10.1115/ht2016-1033
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study and Analysis of Dropwise Condensation Using Quartz Crystal Microbalance

Abstract: This work reports a novel Quartz Crystal Microbalance (QCM) based method to analyze the droplet-micropillar surface interaction quantitatively during dropwise condensation. A combined nanoimprinting lithography and chemical surface treatment approach was utilized to directly fabricate the micropillar based superhydrophobic surface on the QCM substrate. The normalized frequency shift of the QCM device and the microscopic observation of the corresponding nucleation, drop growth, and drop coalescence processes cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…There has been a long history for quartz crystal microbalance (QCM) resonators to serve as a mass-frequency transducer, which vibrates in a thickness shear mode (TSM) mode. Own to its high sensitivity, stability, simple structure and low cost, QCMs has been widely applied in bio- or chemical sensing field [ 1 , 2 , 3 , 4 ]. Usually, the QCM resonator is composed of an ATcut quartz crystal piece and two metal film electrodes coated onto double surfaces of the quartz crystal chip.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a long history for quartz crystal microbalance (QCM) resonators to serve as a mass-frequency transducer, which vibrates in a thickness shear mode (TSM) mode. Own to its high sensitivity, stability, simple structure and low cost, QCMs has been widely applied in bio- or chemical sensing field [ 1 , 2 , 3 , 4 ]. Usually, the QCM resonator is composed of an ATcut quartz crystal piece and two metal film electrodes coated onto double surfaces of the quartz crystal chip.…”
Section: Introductionmentioning
confidence: 99%
“…Su et al developed the QCM technique to study the liquid/solid interaction during dropwise condensation on flat and micropillar structures with different hydrophobicities. His results demonstrated the capability of the QCM to analyze the dynamic of the condensation process in comparison to the optical imaging technique. Wang et al used a QCM to characterize the liquid penetration on a micropillar pillar structure with superhydrophobic state and the QCM response was quantified numerically and experimentally. Their experimental results showed that the meniscus pendant depth of liquid using the QCM were in good agreement with results obtained from cryogenically focused ion beam/scanning electron microscope (cryo FIB-SEM) .…”
Section: Introductionmentioning
confidence: 99%
“…QCM is a well-known high precision resonator with a measurement accuracy in the nano-gram range. The sensor has a high sensitivity, simple structure, and can be used in real time without interruption in gas or liquid environments [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%